Three Dimensional Correction of Severe Rigid Neurofibromatosis Scoliosis. Issue 1 (April 2016) - Koptan, Wael; El-Sharkawi, Mohammad; ElMiligui, Yasser
Introduction: The surgical management of severe rigid dystrophic neurofibromatosis curves is a demanding procedure with uncertain results. Several difficulties are present in such patients including a poor bone stock, sharp angulation of these curves and the delicate nature of the dural sac. The aim of this work is to review the clinical and radiographic outcome of three-dimensional correction of severe rigid neurofibromatosis curves analyzing its efficacy, safety and possible complications. Materials and Methods: The results of 32 patients with severe rigid neurofibromatosis deformities were retrospectively reviewed. Patients were followed-up for a minimum of 3 years; an average of 6.5y (range 3 – 9y). The average age was 14 years (range 11 – 19y). All patients had typical dystrophic curves and the apex of the deformity was dorsal (13 patients); dorsolumbar (14 patients) and lumbar (5 patients). All patients had a two staged procedure; an anterior release followed by posterior instrumentation augmented by sublaminar wires. The wires were placed immediately below the proximal anchor and several sublaminar wires at the apex of the deformity. There were a total of 142 wires with an average of 6.5 wires/ patient (range 5 – 8 wires). Results: The mean Cobb angle of the main curve was 102° before surgery corrected to an average of 39° and the loss of correction had an average of 4°. Sagittal alignment improved from an average of 12° to an average of 47° and rotation was corrected by an average of 34%. There were no dural tears during passage of the sublaminar wires and no neurological or implant related complications. Conclusions: The use of extensive and vigorous anterior release with posterior hybrid instrumentation has proved useful and effective in the treatment of these difficult cases; sublaminar wires allow safe gradual correction and even distribution of forces over multiple anchor points improving the correction achieved and decreasing implant related complications.